Organization-Methodological Conditions of Practical Preparation of Technologists of Food Industry in Colleges - Halus, Oleksandr; Ocheretna, Inna (Pedagogical Discourse, 2016)
Organization-methodological conditions of practical preparation of technologists of food industry in colleges have been revealed in the article: informational, financial-economic, material and technical, scientific-methodological, organization-managerial, social-economic. The structural, aim, contextual and procedural components of multilevel professional preparation, directed to the personality forming, highest possible determination of abilities, realization of professional-educational needs of the students in the system «college – university», have been theoretically grounded. Such basic functions of organizational-pedagogical conditions as: social, prognostic, integrative, economic, research, scientific-technical have been determined. The effectiveness of organizational-pedagogical conditions, which guarantee organization of professional practical preparation in the system «college – university» has been proved. The system of multilevel professional education according to the regional needs in technologists of the enterprises of food industry has been worked out. Scientific-methodological providing of the educational process, which includes normative-legal and educational-methodological complexes, guarantees the organization of educational process in multilevel system of professional practical preparation has been developed. The peculiarity of the modern stage of development of professional education of specialists in the food industry is their practical training in College. Under the market operational environment, the emergence of a large number of small and medium enterprises of the food industry there is the need in professionally mobile, highly skilled, competitive and educated specialists, capable of creative and initiative professional activity, rapid adaptation to the changing production conditions. In the existing system of professional training of specialists (technologists) of the food industry the new demands of socio-economic development; interests of individuals, society and the state; achievements of modern pedagogical science and vocational education are not adequately presented, while under the conditions of development of market relations training of specialists in the field of food industry gains great social and economic significance. In order to meet the demand on the labour market in relevant specialists, it is necessary to create optimal organizational-methodical conditions for modernization and further development of the practical professional training of the future technologists of food industry in colleges. The worked out organizational-methodical conditions of multilevel professional training of technologists of the food industry represent integrative object that provides interconnection at all levels of education (secondary, higher professional education), integrity, continuity, openness and succession of the educational process. Organizational-methodical conditions of professional training of technologists of the food industry include informational, financial-economic, material-technical, scientific-methodical, organizational-administrative, socio-economic conditions. The combination of these conditions allowed conducting the continuity of educational processes ensuring increase of level of education, breeding, competitiveness of graduates on the labour market. Key words: organization-methodological conditions, practical preparation of specialists, components of professional preparation, technologist of food industry, scientific-methodological providing.